Pengaruh Kemampuan Kerja dan Motivasi Kerja Terhadap Daya Saing UMKM di DIY - Ida Uliyah; Muji Mranani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The growth of MSMEs cannot be separated from the competitiveness of products between MSME actors. Competitiveness is an important factor in the success of MSMEs themselves. Several factors that can affect competitiveness include Work Ability and Work Motivation. Both variables are very important in increasing competitiveness which can then accelerate the growth of MSMEs. This study uses the PLS 3.0 Data Analysis method. The results of the study showed that work ability has a positive effect on Competitiveness, while Work Motivation does not affect the Competitiveness of MSMEs in DIY.